DNA Computing (International Journal of Engineering and Computer Science, 2017)
Biology and computer science are two different sciences but both sciences are sister.In this research I intend to show that how biology is used in computation. In future, how biology is used to make enhancement in computer sciences. Use of biology in computer science is known as biological computation. Biological computation is a subfield of computer science and computer engineering using bioengineering and biology to build computers. One of them is DNA computing. DNA computing is a way that aims at harnessing individual molecules at the nano-scopic level for computational purposes. Computation with DNA molecules possesses interest for researchers in computers and biology. Due to its vast parallelism and high-density storage facility, DNA computing approaches are used to solve many problems. DNA has also been explored as an excellent material and a fundamental building block for building large-scale nanostructures, constructing individual Nano mechanical devices, and performing computations